ANALISIS FAKTOR- FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN - Erick Hernandez; Augustpaosa Nariman (Jurnal Paradigma Akuntansi, 2023)
The purpose of this study was to analyze the effect of capital structure, profitability, independent board of commissioners, and firm size on firm value in manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2018-2020 period. This study uses a sample of 78 manufacturing companies listed on the Indonesia Stock Exchange. The sample has been selected through purposive sampling method so that the total data obtained is 234 data (in three years). In conducting data processing, this research uses Microsoft Excel and Eviews software version 12. The panel data regression model chosen in this study is the fixed effect model (FEM). The results of this study indicate that profitability has a significant positive effect on firm value. Meanwhile, capital structure, independent board of commissioners and firm size have no significant effect on firm value.